C-Arm Guided Epidural Steroid Injection: An Effective Treatment for Patients with Radiculopathy in Tertiary Level Hospital of Bangladesh - Ali, Tamjid; Khasru, Moshiur Rahman; Salek, AKM; Sikdar, Alauddin; Haque, Quazi Tamanna (TAJ: Journal of Teachers Association, 2023)
Introduction: Epidural steroid injections (ESI) have been utilized for over 50 years in the conservative therapy of prolapsed lumbar intervertebral discs. However, controversy persists regarding their effectiveness in reducing pain and improving function, with literature supporting and opposing them. Aim: To study the effectiveness of epidural steroid injection in treating pain caused by a prolapsed lumbar intervertebral disc and compare the effectiveness between caudal, transforaminal, and interlaminar injection routes. Materials and Methods: A total of 152 patients with back pain with Radiculopathy with a lumbar disc prolapse confirmed on MRI were included in the study. Their pre-injection Japanese Orthopedic Association Score (JOA) counted up. In this study, participants were enrolled using a simple randomization procedure (picking a card).in the Department of Physical Medicine & Rehabilitation at BSMMU, Dhaka, from May 2020 to April 2021. Among 152 patients were intervenes as transforaminal (n=62), caudal (n=53), and interlaminar (n=25) approach with subsequently received epidural steroids as methylprednisone. Twelve individuals were dropped from the trial because they failed to show up for their scheduled therapy. Results: The prevalence increased dramatically, leading to a JOA Score at 12 months following injection via any of the three methods 53 (37.26%) via the caudal pathway, 62 (44.21%) via transforaminal, and 25 (18.53%) via interlaminar. At six months and 12 months post-injection, the transforaminal route was substantially more efficacious than the caudal (p=0.01) and interlaminar routes (p=0.03). Comparing the caudal and interlaminar methods yielded no statistically significant difference (p=0.36). Conclusion: In the current study, methylprednisone epidural injections effectively treat radiculopathy and back pain caused by a herniated lumbar disc. All three injection techniques are adequate, with the best result obtained by the transforaminal route. TAJ 2022; 36: No-1: 113-118